In search of good practice : learning from the effective teachers in Malaysia - Konting, Mohd Majid (1993)
This paper reports a research on classroom teachimg four years after the implementation of the Integrated Secondary School Curriculum (ISSC)in Malaysia. It considers some of the practices of 16 mathematics teachers of 12-13 years old students who are identified as effective through systematic observation. Since existing secondary school teachers have already developed their own sustainable approach towards good practice, it was argued that effort had to be made to reduce the mismatch between what ought to be prescribed by the curriculum and what ought to be practised by the teachers.